Zooplankton assemblages of Sungai Sibu, Sarawak - Nur Athirah, Binti Saidi (Universiti Malaysia Sarawak, UNIMAS, 2012)
A study of zooplankton in Sungai Sibu was carried out to determine the zooplankton composition, diversity and to record selected water quality parameters. Sampling was done on 27th Nov 2011 and 2nd February 2012. A total of 16 genera belonging to 7 class and 6 group were identified in this study. The groups were Copepoda, Anotraca, Rotifera, Protozoa, Annelida and Artropoda.The group of Copepoda was recorded as dominating the zooplankton communities in all stations which made up of 94% of total abundance. The zooplankton percentage followed the orders : Copepoda > Anostraca > Rotifera > Annelida > Protozoa > Artropoda . Limnocalanus and Calanoid were the common genera that found from every sampling site. Species diversity values range from 0.0377 to 0.920. Turbidity and pH have a strong positive correlation with zooplankton diversity. The correlation value for turbidity is (r= 0.734) and pH (r= 0.650).